Digital Storytelling Animation Media with Minimum Competency Assessment to Enhancing Students Folktales Reading Comprehension - Faizah, Auliya Nurul; Purwati, Panca Dewi; Murtini, Tri (Jurnal Ilmiah Sekolah Dasar, 2024)
This research is motivated by observational data indicating the low learning outcomes of second-grade students in the competency of reading to folktales, which is attributed to the limited use of media in teaching. Therefore, this research aims to developed an instructional tool: digital animation storytelling media with Minimum Competency Assessment (MCA). The research method employed in this study was Research and Development (R&D), utilizing the ADDIE model. This study involved a class teacher and 26 learners in grade II of an Elementary School. The primary objective of this research was to analyze the feasibility and effectiveness of the digital animation storytelling media with MCA for the second-grade class in enhancing the competency of reading to folktales. Data were collected using a questionnaire to assess media feasibility and pretest-posttest questionnaires to measure the media's effectiveness. The results of the media feasibility assessment, based on the questionnaire, obtained a percentage of 90%, indicating "Very Feasible" according to content experts, while media experts rated it at 84%, indicating "Eligible." Regarding the effectiveness of the media, as assessed through pretest-posttest questionnaires, the N-Gain test revealed an average improvement of 0.48 on a small scale with an average difference of 22.5. Based on these findings, it can be concluded that the digital animation storytelling media with MCA for the second-grade class is not only suitable for instructional use but also effectively enhances students' learning outcomes in the competency of reading to folktales.